Alternative realities: Explaining security in the Asia-Pacific. Issue 3 (1st February 2017) - Beeson, Mark
Abstract: The central argument of this article is that constructivists in particular underestimate or even ignore the importance of the 'real' structural inheritance that shapes state (and the political elites that represent them) behaviour. Even though the future is indeterminate, some outcomes are decidedly more likely than others, especially where policymakers believe they inhabit a strategic universe of zero sum outcomes and where self-reliance and assertion remain important. I suggest that 'critical realism' offers a way of accounting for the institutional structures that shape international behaviour. The first half of this article makes the case for a critical realist approach. The second half illustrates the possible importance of this claim with reference to the contemporary geopolitics of the Asia-Pacific region.